PRAKTIK AGROFORESTRI TRADISIONAL (LAMPOH) DI ACEH BESAR: MENILAI POTENSI DAN PEMANFAATAN OLEH MASYARAKAT DI KECAMATAN SIMPANG TIGA - Durrah Hayati; Fahmy Armanda; Maryam Jamilah; Ida Rosita; Ali Muhammad Muslih (JURNAL AGRIMENT, 2023)
Traditional agroforestry systems (TAFS) are longstanding practices characterized by the absence of intentional agricultural intensification. In Aceh, Indonesia, a specific type of TAFS known as "lampoh" is practiced, representing a multispecies agroforestry system deeply rooted in Acehnese culture. This study aimed to identify the plant species found in traditional agroforestry gardens in Aceh Besar and explore their utilization by the local community. The study was conducted in three villages within the Simpang Tiga District of Aceh Besar, utilizing primary and secondary data collection methods. Direct observations and interviews with community members were employed to identify plant species and gather insights into Historis and present practices. The study revealed a traditional multistory agroforestry system, Lampoh, consisting of diverse tree species and perennial plants. Interviews identified 24 Historisly and currently cultivated and utilized plant species, with some species no longer present in the agroforestry gardens of the studied villages. The decrease in agroforestry garden utilization was attributed to shifts in primary income sources, modernization, and urbanization, which provided alternative livelihoods and preferences. To ensure the sustainability of agroforestry practices, efforts should integrate agroforestry into evolving livelihood systems, raise awareness about its importance, and improve market access, taking into account the changing economic landscape and community preferences. This will help preserve the contributions of agroforestry to food security, ecological diversity, and economic well-being.